A Religio - Philosophical Analysis of the Contemporary Moral Dilemmas in Family Values with Special Reference to Key Bioethical Issues - Paul Rohan, J.C. (Sri Lanka National Seminary Journal, 2019)
A moral dilemma is a situation of internal conflict when one has to choose between a set of actions and have moral reasons for these actions. Moral dilemma is created when one is in a perplexed situation could find any action to be right and wrong at the same time and have difficulty in choosing the correct action. The study of moral dilemmas entails a far greater complexity because of its wider and in-depth prevalence in the contemporary society. Everywhere the human beings live lives that are, to an extraordinary extent, caught up with the breakaway of values. The human society has lost the values that were preserved as necessary for a decent human living and the human race seems compelled to concede that there is only a subtle difference between cannibalism and civilization. In this research, an attempt is made to study the moral dilemmas created by a recent factor which was brought due to the fast growth in science and technology, which is none other than bioethics. A religio-philosophical study is made on the moral dilemmas in family values created by the bioethical ventures in order to analyze the root causes of these issues and to caution their impending dangers to the human race. The title entails some areas which need to be qualified: contemporary moral dilemmas in family values; the moral dilemmas created by bioethical issues; and a religio-philosophical analysis of them. These areas are to be treated separately in order to bring about the full project of the title.
Keywords: Ethos; Bioethics; Paradigms; Intervention; Personalistic; Magisterium; Implication; Wholistic